Elaboración de un manual de estudio de destrezas ortográficas para el mejoramiento del rendimiento académico de los estudiantes de octavo año de educación básica de la Unidad Educativa Fiscal Experimental del Milenio “Penipe”, en el año lectivo 2014 – 2015 - Villegas Chunata, María Teresa (2016)
To enter this research field split the problem in the Experimental Education Unit Fiscal Goals "Penipe" young students of the eighth year of basic education have no skills in managing spelling which hinders academic performance; for it was set as the general objective to determine the improved academic performance by developing a manual spelling study supported specific skills. It began with a theoretical framework that focused on the analysis of the two study variables and their respective topics and subtopics; emerging philosophical foundations, epistemological, sociological, psychological, pedagogical, axiological and legal. Previous research study also analyzed with emphasis on the macro, meso and micro; contained within this important section of the terminology used in the two respective variables. In the methodology we started from a non-experimental research design because it was not handled any variable, not laboratory was used, unlike the research allowed to describe the phenomenon that occurs in reality, the types of survey was applied which led us to put running theory and explorative processes, the literature is reflected in the use of several bibliographic references, field led us to move to the scene, ie the Millennium Educational Unit "Penipe". As methods include scientific, inductive - deductive, analytical - synthetic. The population rose to 26 observation units are all young eighth year. The technique used was to gather information and as an instrument survey, the questionnaire based on closed questions and multiple-choice dichotomous, the relevant findings are in the need for manual skills for students in the eighth year of basic education. It concludes with the urgent implementation of the manual